14th AIAA Aviation Technology, Integration, and Operations Conference 2014
DOI: 10.2514/6.2014-3004
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Air Distribution in a Preliminary Design Stage of an Aero-Engine Combustor

Abstract: The design of a modern aero-engine combustor is strongly driven by severe emission regulations. The paper describes an automated preliminary aero-thermal design process for a rich-burn combustor by combining different low fidelity analysis tools in order to speed up the preliminary design loop and provide improved combustor designs. Design evaluation is performed by a knowledge-based preliminary design tool coupled with a network solver. The preliminary design tool provides a 2D geometry model and cooling layo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In order to influence the combustor outline and to optimize the efficiency and emission index, flow settings concerning the internal air distribution will be varied. Relevant design parameters are the air-to-fuel-ratios at injector r a f ,in and primary zone exit r a f ,pz , length of primary and secondary combustion zones represented by the relative position of the related mixing ports (γ pp , γ sp ), and the style of the primary and secondary mixing ports (s pp , s sp ) similar to [18]. The air-to-fuel ratios are related to the local mass flows at the injector, as well as primary zone exit, and are normalized by the fuel mass flow.…”
Section: Combustor Design Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to influence the combustor outline and to optimize the efficiency and emission index, flow settings concerning the internal air distribution will be varied. Relevant design parameters are the air-to-fuel-ratios at injector r a f ,in and primary zone exit r a f ,pz , length of primary and secondary combustion zones represented by the relative position of the related mixing ports (γ pp , γ sp ), and the style of the primary and secondary mixing ports (s pp , s sp ) similar to [18]. The air-to-fuel ratios are related to the local mass flows at the injector, as well as primary zone exit, and are normalized by the fuel mass flow.…”
Section: Combustor Design Problemmentioning
confidence: 99%
“…), and the style of the primary and secondary mixing ports ( , ) similar to [18]. The air-to-fuel ratios are related to the local mass flows at the injector, as well as primary zone exit, and are normalized by the fuel mass flow.…”
Section: Combustor Design Problemmentioning
confidence: 99%
“…Che et al [12] made calculations for both steady and transient state problems by using the component method and network method toward series and parallel networks. They showed that the whole engine model simulated by the component method is suitable for observing the safety of engine influenced by the dynamic characteristic of the secondary air system Angersbach and Bestle [13] described an automated preliminary aero-thermal design process for a rich burn combustor by combining preliminary design tool, 2D geometry model coupled with a 1D network solver in order to speed up the preliminary design loop and provide improved combustor designs. The 1D network solver then would calculate the air distribution inside the combustor for two different combustor cooling schemes.…”
Section: Rama Kumar and Prasadmentioning
confidence: 99%